An Analysis of Cash and Receivables Turnover Effect Towards Company Profitability - Titik Purwanti (International Journal of Seocology, 2019)
The purpose of this study was to analyze the effect of cash turnover, accounts receivable turnover on profitability. The profitability of manufacturing companies in Indonesia is influenced by various financial factors that can be measured using financial ratios. The research data was obtained from the company's annual report during 2011-2015 using a purposive sampling method which included an independent auditor's report and financial statements of manufacturing companies in the consumer goods and textile industry sectors. The sampling method used was purpose sampling and obtained 32 companies as samples. The independent variable in this study is cash turnover and accounts receivable turnover while the dependent variable is profitability. Methods of data analysis using the classic assumption test, multiple linear regression analysis, F test, and t test. The results of the analysis of this study are the cash turnover and accounts receivable simultaneously affect profitability. Partially, the two variables also affect profitability.